2020
DOI: 10.1051/e3sconf/202021019003
|View full text |Cite
|
Sign up to set email alerts
|

Features of self-presentation of modern young people in social networks

Abstract: In the digital age of a transitive society, interaction between people is undergoing significant changes. Many researchers talk about the virtualization of modern society, in which visual communication comes to the fore. However, despite the prevalence of the above-mentioned processes, questions remain about strategies for presenting themselves to society using social networks, and how people position themselves when publicly presenting themselves in an online environment. As part of the empirical study, the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Within the framework of modern realities, it is debatable whether Internet addiction is an independent diagnosis or rather the product of other existing disorders, such as depression, anxiety, ADHD, or pattern control disorders [1,3,6,7,8,13,14,15,16,17]. A fairly large number of authors believe that Internet addiction is a behavioral addiction [15,17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Within the framework of modern realities, it is debatable whether Internet addiction is an independent diagnosis or rather the product of other existing disorders, such as depression, anxiety, ADHD, or pattern control disorders [1,3,6,7,8,13,14,15,16,17]. A fairly large number of authors believe that Internet addiction is a behavioral addiction [15,17].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies on the treatment of Internet addiction can be noted, which are based on interventions and strategies used in the treatment of disorders associated with the use of psychoactive substances [1,3,6,7,8,13,14,15,16,17,19,20,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of studies devoted to the semantic sphere of youth has shown insufficient knowledge of the meaning-life orientations of youth in the projection on the social sphere [4,5].…”
Section: Introductionmentioning
confidence: 99%